Touch sensors for 3D-printed automobile electronics: analysis, synthesis, and electromagnetic compatibility issues - Morgado, Davide Manuel Ribeiro (2021)
The Additive Manufacturing has been developing more and more, providing numerous advantages to the industry. Among such advantages is the use of materials with conductive properties combined with 3D printing techniques, which enables development of new devices embedded in plastic elements. One of the industries where Additive Manufacturing methods can be applied most successfully is the automotive industry. The electrification of cars, connected cars, autonomous driving, equipment enriched with sensors for better comfort are some of the challenges that this industry faces. Thus, innovation is made in the sense of developing new products to meet the presented challenges, always focusing on the user. Thus, this Master Thesis aims to study, explore and expand these concepts and apply them to the development of a touch sensor, as well as to understand what are the problems of compatibility and electromagnetic interference that can be encountered in automotive environment, specifically, in a smart door for a car. This work begins with the study of Additive Manufacturing methods, the types of measurements for a touch sensor, the sensor designs, and the electromagnetic compatibility and interference issues relevant for such sensors. Useful tools are developed to calculate the sensor capacitance, inductance and resonant frequency. Also, a script is developed to obtain the structural parameters for the resonant frequencies in desired ranges. These tools made it possible to develop a macro to automate creation of 3D structures in CST Studio Suite and thus to be able to simulate such structures for a large set of obtained parameters. Based on the simulations, we designed two sensor structures operating at the desired frequencies and, with the 3D structures ready, moved on to the experimental measurements, producing a PCB prototype for each structure. Thus, by completing these procedures it was concluded that the experimental measurements allowed us to test the developed tools and models and to validate the entire study.